2014
DOI: 10.1080/17470218.2013.820763
|View full text |Cite
|
Sign up to set email alerts
|

Picture–Word Interference Reveals Inhibitory Effects of Syllable Frequency on Lexical Selection

Abstract: While previous research has shown that high syllable frequency can facilitate speech production at the level of phonological/phonetic encoding, little is known about its influence on prephonological processes, specifically lexical selection. The current study used a picture-word interference (PWI) task to (a) shed light on the stages of lexical access where syllable frequency is relevant, and (b) inform as to whether lexical selection is accomplished via competition among activated word options. Participants n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Within the NST and TDH model, the increased ease in learning HF first-syllable names results from the increased use of the phonological components, which strengthens their connections and makes them easy to access and learn (e.g., James & Fogler, 2007). As described by Farrell and Abrams (2014):. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the NST and TDH model, the increased ease in learning HF first-syllable names results from the increased use of the phonological components, which strengthens their connections and makes them easy to access and learn (e.g., James & Fogler, 2007). As described by Farrell and Abrams (2014):. .…”
Section: Discussionmentioning
confidence: 99%
“…Venuto’s (2019) unpublished experiment tested whether a “downstream” benefit of greater phonological frequency would emerge during name–face association learning. HF syllables essentially have long-term practice effects that strengthen all connections to and from those nodes, facilitating their access (Farrell & Abrams, 2014). These strengthened connections should in turn make learning a name with HF sound sequences easier than learning one with LF sound sequences.…”
mentioning
confidence: 99%
“…The inhibitory effect of token syllable frequency has been obtained in speech production as well. For example, Farrell and Abrams [ 71 ] reported an inhibitory effect of syllable frequency in successful speech production (see also [ 72 ] for inhibitory influences on tip-of-the-tongue resolution). Furthermore, they found that inhibitory syllable frequency effects were more pronounced in the presence of phonologically related distractors and for targets of low WF in PWI tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Because homophone regularity influences orthographic encoding, we would expect increased errors when competitors have regular spellings because of stronger connections to these regular spellings, relative to competitors with irregular spellings. However, evidence suggests that older adults may have reduced activation to phonological competitors (e.g., Abrams, Trunk, & Merrill, 2007; Burke et al, 1991; Farrell & Abrams, 2010), which would lead older adults to have fewer errors than younger adults when spelling unambiguous homophones. This reduction in activation to competitors has been observed in spoken production via tip-of-the-tongue (TOT) states, where older adults have fewer alternate words come to mind than younger adults, despite having more TOT states (e.g., Burke et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Older adults also are less likely to resolve their TOTs than younger adults following presentation of a phonologically related word (Abrams et al, 2007; White & Abrams, 2002), suggesting that older adults transmit less activation from a phonological prime to the TOT's lemma to enable retrieval. Recent research (Farrell & Abrams, 2010) has also shown that older adults less effectively transmit activation to phonological competitors than younger adults in a picture-word interference task.…”
Section: Methodsmentioning
confidence: 99%